Analysis on Genetic diversity of Threatened Medicinal epiphyte Pleione maculata from different Geographical habitats using RAPD and ISSR marker - Sympli, Hakani D.; Borah, Vedant Vikrom (Indian Forester, 2025)
Pleione maculata is a threatened medicinal epiphyte, as pseudobulbs are used to cure headaches, stomachaches and liver diseases. There are currently no reports on genetic diversity studies of P. maculata utilizing a molecular marker system that is relevant for conservation and breeding. Therefore, patterns of genetic variability and intraspecific similarities across P. maculata from three different geographical distributions were assessed in this study using Random Amplified Polymorphic DNA (RAPD) and Inter Simple Sequence Repeat (ISSR) markers. From the 16 RAPD and 2 ISSR markers evaluated, a total of 96 distinct and reproducible DNA amplicons were generated. The morphological dissimilarity matrix was calculated using the Mantel test and Nei’s genetic diversity coefficient. The highest computed PIC value for RAPD was 0.44, whereas the highest PIC values for ISSR were 0.48. The two sets of molecular markers used were highly correlated, with a correlation Mantel statistic (r) of 0.79, indicating high marker efficiency in population genetic studies. The results of this study will provide a basis for understanding genetic link, genetic variation and strategies for establishing a germplasm collection for the species’ conservation, management, breeding, and hybrid production within the P. maculata population.